2017
DOI: 10.1021/acs.jafc.6b04790
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyrimidine Tagged Silver Nanoparticle Based Fluorescent Immunoassay for the Detection of Pseudomonas aeruginosa

Abstract: A simple pyrimidine-based fluorescent probe (R)-4-(anthracen-9-yl)-6- (naphthalen-1-yl)-1,6-dihydropyrimidine-2-amine (ANDPA) was synthesized through the greener one pot reaction and characterized by IR, NMR, and ESI-Mass. Glucose stabilized silver nanoparticles (Glu-AgNPs) were also synthesized and characterized using UV, IR, XRD, SEM, and TEM. When ANDPA was tagged with Glu-AgNPs, the fluorescent intensity of ANDPA decreased drastically. When the monoclonal antibody (Ab) [immunoglobulin G (IgG)] of Pseudomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…5658 Therefore, the fluorescent intensity of the immunoassay was increased. 51,59,60 Therefore, based on these UV–vis and emission spectral changes, it is confirmed that two interesting mechanisms such as inhibition of twisted ICT and AIE are existing during the formation of anti-AH–AHC and AH/anti-AH–AHC immunocomplexes, respectively, under optimized conditions (Scheme 1).…”
Section: Results and Discussionmentioning
confidence: 62%
“…5658 Therefore, the fluorescent intensity of the immunoassay was increased. 51,59,60 Therefore, based on these UV–vis and emission spectral changes, it is confirmed that two interesting mechanisms such as inhibition of twisted ICT and AIE are existing during the formation of anti-AH–AHC and AH/anti-AH–AHC immunocomplexes, respectively, under optimized conditions (Scheme 1).…”
Section: Results and Discussionmentioning
confidence: 62%
“…Recently, efforts have been devoted to the rapid and sensitive detection of P. aeruginosa using various approaches. Different recognition elements are used, including monoclonal antibody ( Ellairaja et al, 2017 ), DNA aptamers ( Zhong, Gao, Chen, & Jia, 2020 ), fluorescent organic nanoparticles ( Kaur, Raj, Kaur, & Singh, 2015 ). These elements enhance the sensitivity for P. aeruginosa detection and reduce the assay time.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the detection schemes reported for P. aeruginosa focus on whole pathogen detection [ 142 146 ] with the work of Melanie et al [ 139 ], discussed above, on 16s rRNA detection being an outlier. In addition, to oligonucleotide recognition elements [ 139 , 142 144 ], antibodies [ 145 , 147 ] and bacteriophages [ 146 ] have also been used for specific detection of P. aeruginosa .…”
Section: Analytesmentioning
confidence: 99%